Analysis of Role of Computed Tomography of Brain in Children with Partial Seizures at a Tertiary Care Hospital - Ghanshyam G. Patel; S R Chauhan (Asian Journal of Medical Radiological Research, 2014)
Background: Partial seizures are relatively common in pediatric populations and are categorized into two distinct types: simple partial seizures, which do not involve a loss of consciousness, and complex partial seizures, which do result in altered consciousness. Hence; the present study was conducted to analyze role of computed tomography of brain in children with partial seizures at a tertiary care hospital. Materials & Methods: A cohort of 100 children diagnosed with seizure disorders, specifically those experiencing partial motor seizures, was evaluated in a prospective manner. The participants ranged in age from 1 to 12 years. Only those exhibiting partial seizures characterized by predominantly focal motor symptoms were included in the study. The classification of seizures was determined through comprehensive medical history and clinical assessments, alongside the results of brain CT scans for all subjects. Standard laboratory investigations were performed, which included a complete blood count with erythrocyte sedimentation rate, basic renal and liver function tests, a Mantoux test, and a chest X-ray. Additionally, cerebrospinal fluid analysis was conducted via lumbar puncture and/or electroencephalography when clinically warranted. A contrast-enhanced CT scan of the brain was also performed, utilizing a system capable of 128 slices per rotation. Results: A total of 100 children were evaluated. Mean age of the children was 8.9 years. Focal seizures were seen in 82 percent of the children. Fever, headache, vomiting, cyanosis, visual disturbances, altered sensorium, papilledema and cranial nerve palsy was seen in 48 percent, 45 percent, 42 percent, 5 percent, 2 percent, 46 percent, 18 percent, and 14 percent of the patients. CT scan of brain was normal in 29 children (29%) and was abnormal in 71 children (71%). Tuberculoma, Neurocysticercosis, Vascular lesions and Congenital (Gliosis) lesions were seen on CT in 12 percent, 2 percent, 12 percent and 3 percent of the patients respectively. Significant correlation was seen while correlating computed tomography findings with types of seizures. Conclusion: Partial seizures characterized by significant motor manifestations exhibit a notably increased prevalence of underlying structural causes, particularly in relation to neurological infections. Furthermore, there exists a positive correlation between clinical observations and findings obtained from CT scans.